Isolasi dan Pengukuran Aktivitas Enzim Bromelin dari Ekstrak Kasar Bonggol Nanas (Ananas comosus) pada Variasi Suhu dan pH - Masri, Mashuri (Biogenesis, 2014)
This study was conducted to isolate the bromelain enzyme from pineapple weevil (Ananas comosus) and measure the protein and enzyme activity of bromelain with gelatin substrate. Research stage involves determining the protein content of the bromelain enzyme in the treatment of ammonium sulfate precipitation by 10-60% concentration and determination of bromelain enzyme activity at various pH 4.0; 5.0; 6.0; 7.0 and 8.0, with the incubation time of 10 minutes at a temperature of 650 C. Each stage performed three repetitions and analyzed using spectrometry. The results obtained showed the highest protein content in precipitation with ammonium sulfate 60% in the amount of 37.214 mg / ml and the optimum pH of bromelain enzyme activity at pH 7.0 with the value of the activity of 1,081 units / gram.Keywords: ammonium sulfate precipitation, bromelain enzyme, pineapple weevil (Ananas comosus),pH